Characterization and Pathogenicity of Fusarium oxysporum as the Causal Agent of Fusarium Wilt in Chili (Capsicum annuum L.) - REJEKI SITI FERNIAH; BUDI SETIADI DARYONO; RINA SRI KASIAMDARI; ACHMADI PRIYATMOJO (Microbiology Indonesia, 2014)
Fusarium wilt is a serious disease attacking chili plants in Central Java which cause lost of chili productivity. Fusarium wilt is caused by pathogenic fungi Fusarium oxysporum, which is host specific. The objectives of this research were to characterize the pathogenic F. oxysporum as the causal agent of fusarium wilt in chili plants and to observe the virulence of the pathogen. Fungal pathogen was isolated from Tawangmangu as an endemic area of fusarium wilt in Central Java. The fungi was characterized morphologically and identified molecularly by its internal transcribed spacer regions (ITS regions). Pathogenicity test was done to observe the virulence of the pathogen. One pathogenic strain was isolated from Tawangmangu, Karanganyar and was identified Â morphologically and molecularly as F. oxysporum. Â